(untitled) (Trento Student Law Review, 2025)
Dear Readers, When one thinks of a university law journal, the mind often turns to an exclusively editorial project. Yet the Trento Student Law Review is, above all, a community. A reality in which every editor is also a member, and every member contributes—with their time, dedication, and ideas—to sustaining a structure that evolves day by day. Today, we are proud to present the first issue of Volume 7. This edition is the result of collective work that goes far beyond editorial activity. In recent months, our association has launched new initiatives that reflect the vitality of our project. One particularly meaningful milestone has been the launch of a new series of events, designed to build a concrete bridge between students and the professional world. The first event, focused on the impact of digital technologies on legal writing, inaugurated a dialogic format that emphasizes participation and mutual exchange. It was an intense and necessary moment, one that gave shape to a simple yet powerful idea: law is not learned solely through books, and legal education does not end in the classroom. Another important milestone was our participation, as an editorial board, in the conference held as part of the 2025 Doctoral School of the PhD Programme in Private Autonomy, Business, Labour, and the Protection of Rights in a European and International Perspective at Sapienza University of Rome. It was an honour to represent our journal in such a stimulating context, alongside other student-led law journals from across Italy. The exchange of experiences enriched us deeply, allowing us to reflect on our role within the academic landscape—as students who choose to actively engage in legal scholarship, bringing a critical and constructive perspective both within and beyond the editorial process. The contributions published in this issue address complex and pressing legal topics, offering diverse and thought-provoking viewpoints. Our editorial team—comprising dozens of internal editors, supported by external reviewers and visiting editors—has worked with its usual scholarly rigour to ensure the quality of each publication, fully aware that every article contributes to a broader dialogue between law, society, and culture. I would like to thank the authors who placed their trust in our journal, the reviewers who supported us with precision and generosity, and all the editors who make this project possible every day. A special thanks goes to the members of the board, who face daily challenges with teamwork and unwavering commitment, demonstrating how much they care about this shared endeavour. With the hope that this new issue may offer insights for reflection, dialogue, and growth, I wish you an inspiring read. Kind regards, Rossella Borella Editor-in-Chief